Ética Sexual Cristã e Moral Sexual Familiar em João Paulo II e em casais da Pastoral Familiar João Pessoa. - Lima, Carlos Emanuel Cardoso de (2021)
This thesis entitled Christian Sexual Ethics and Family Sexual Moral in John Paul II and in João Pessoa Family Pastoral couples, sought to investigate how Catholic sexual and marriage morals based on the teachings of John Paul II constitute a practical parameter in the realization of family life and the experience of sexuality. The choice made by the moral teaching derived from the teaching developed by John Paul II is justified by the fact that it has been a milestone in relation to this issue. To achieve the desired goal, we follow a historical line capable of seeing how the Pontificate of John Paul II fits into a tension in both the moral and ecclesiological perspectives. It should be noted that there is a paradoxical rupture in the Pontificate of Paul VI, because, although he was the Pontiff to carry out the Second Vatican Council, he presented to the world a perspective of moral doctrine that can be considered at least controversial in relation to the proposals of dialogue seen in the Second Vatican Council and, consequently, despite the emancipatory movements of the 1960s. John Paul II is aligned with this perspective presented in Humanae Vitae and the reference in constituting his doctrinal vision on Sexual and Family Moral. It is a documental, bibliographic and comparative analysis, supported by the magisterial and quantitative documents for conducting a research with a group of people from the Family Ministry of the Archdiocese of Paraíba. With this work, subsidies are offered for a wider knowledge of how the Church has constituted and maintains its valuable doctrinal treasure on Moral, as well as this, so that to remain faithful to a long Tradition, it needs to dialogue with the contemporary world.